Some Interesting Stories From The Iranian Model of Kidney Transplantation - Tayebi Khosroshahi, Hamid; Bastani, Bahar (Urology Journal, 2020)
In this short communication we briefly discuss some aspects of organ shortage for transplantation with a brief characterization of the Iranian model of kidney transplantation, and we present 3 interesting stories related to this model.